The effect of cesarean delivery on the neonatal gut microbiome in an under-resourced population in the Bronx, NY, USA - Sandra E. Reznik; Ayodele J. Akinyemi; David Harary; Mariam S. Latuga; Mamta Fuloria; Maureen J. Charron (BMC, 2024)
Abstract Background Neonatal and early-life gut microbiome changes are associated with altered cardiometabolic and immune development. In this study, we explored Cesarean delivery effects on the gut microbiome in our high-risk, under-resourced Bronx, NY population. Results Fecal samples from the Bronx MomBa Health Study (Bronx MomBa Health Study) were categorized by delivery mode (vaginal/Cesarean) and analyzed via 16 S rRNA gene sequencing at four timepoints over the first two years of life. Bacteroidota organisms, which have been linked to decreased risk for obesity and type 2 diabetes, were relatively reduced by Cesarean delivery, while Firmicutes organisms were increased. Organisms belonging to the Enterococcus genus, which have been tied to aberrant immune cell development, were relatively increased in the Cesarean delivery microbiomes. Conclusion Due to their far-reaching impact on cardiometabolic and immune functions, Cesarean deliveries in high-risk patient populations should be carefully considered.